Incomplete Cervical Dilation with Fetal Mummification in Goat: A Case Report - Warghat, Chinmay; poornima, Poornima Dwivedi; sahu, uttam kumar; Rele, Gauri; Sushil, Sushil Kumar (Animal Reproduction Update, 2024)
The current case details the successful management of dystocia in a goat due to  incomplete cervical dilation and fetal mummification. The ‘Referral Veterinary  Polyclinic’, ICAR-IVRI, Izatnagar received the animal, which had a history of  brownish-red vaginal discharge and straining for 5 h. Per-vaginal examination  revealed a fetal mass lodged in the reproductive tract with incomplete cervical  dilation. Induction therapy was administered to facilitate cervical dilation,  allowing for the manual extraction of the mummified fetus. After three days of  postoperative treatment, the goat recovered without complications.
Keywords: Dystocia; Fetal mummification; Valethamate bromide